Loss of interplane correlation in Bi2Sr2CaCu2O6 single crystals - Arribére, A.; Pastoriza, H.; Goffman, M. F.; de la Cruz, F.; Mitzi, D.B.; Kapitulnik, A. (American Physical Society, 1993)
Fil: Arribére A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina